Testing the modifiability of episodic future thinking and episodic memory among suicidal and nonsuicidal adolescents - Pauline Goger; Rachel J. Nam; Nathan Lowry; Kerri‐Anne Bell; Neha Parvez; Olivia H. Pollak; Donald J. Robinaugh; Daniel L. Schacter; Christine B. Cha (Wiley, 2024)
Abstract Background Despite increased attention on treatment and prevention for suicidal adolescents, we know little about potential intervention targets. Episodic future thinking-the ability to imagine detailed, personal, and future‐oriented events-is a modifiable cognitive process that has been linked with suicidal ideation (SI) in adolescents. However, until now its modifiability has only been tested in adults. Method Adolescents (N = 176, ages 15-19; 71% SI) completed performance‐based measures of episodic future thinking (i.e., Experimental Recombination Paradigm) and memory immediately before and after an Episodic Specificity Induction (ESI). Results Adolescents produced a greater number of future episodic details after (vs. before) the ESI but showed no change in non‐episodic details (e.g., semantic information). Patterns of change in episodic future thinking were not moderated by SI history. Adolescents overall did not demonstrate change in past episodic detail counts after the ESI. However, there were select moderating effects of SI history on this effect. Conclusion Results show that episodic future thinking can change immediately following an episodic specificity induction among adolescents, regardless of whether they have previously experienced SI. This demonstration of within‐person change constitutes a foundational first step in examining malleability of episodic future thinking in adolescents and offers preliminary evidence of a cognitive mechanism that may be leveraged in service of reducing adolescents' SI.